UNDERSTANDING ANALYSIS AND TEACHER PREPARATION IMPLEMENT CURRICULUM 2013 - Siti Halimah Halimah (State Islamic University of North Sumatra Indonesia, 2018)
This research aims to describe : understanding, approval, readiness, and preparation of teachers implementing curriculum 2013; inhibiting factors and support implementing curriculum 2013. The type of research used in this research is a survey with its informants are PAI (Islamic Religious Education) teachers who are assigned to various schools and madrasahs who are attending Starta-2 education at UIN-SU Postgraduate. Data collection tools used in this research are tests, questionnaires, and interviews. Research findings: (1) understanding of good category PAI teachers; (2) The teacher approval to implement curriculum 2013 of 18 people (95%) answered agree and as many as 3 people (5%) answered less; (3) teacher readiness in implementing curriculum 2013 as many as 19 people (97%) ready to implement and as many as 2 people (3%) not ready; (4) preparatory steps of the teacher: (a) learn the essence of curriculum 2013, design Lesson Plan (RPP), media & assessment techniques, read the rules, engage in the KKG; (5) inhibiting and supporting factors implementing curriculum 2013: (a) lack of facilities & infrastructure, (b) lack of teachers’ books and students’ books, (c) lack of teacher knowledge (d) time limitations. Driving factors: (a) there are teachers' books and students’ books, (b) there is support from the manager, (c) there is provision (c) having adequate awareness, and adequate skills